Odrzucenie? Ambiwalencja? Afirmacja? Wartość macierzyństwa w świetle diagnozy postaw młodzieży szkól średnich Poznania - Włodarczyk, Ewa (Wydawnictwo Naukowe UAM, 2007)
The article encourages the reader to reflect on the problem of motherhood seen in the context of manifold conditions of its location in the hierarchies of values and plans for life of contemporary Poles. The results quoted here of the opinion poll which has been conducted among the highest grades students of Poznań secondary schools are an attempt to discover their attitude towards their own as well other people's motherhood.
Rejection? Ambivalence? Affirmation? The value of motherhood in the light of the diagnosis of attitudes of secondary school children in Poznan
Keywords: młodzież; macierzyństwo; postawa; young people; maternity; attitude